Influence networks and public goods - Dunia López-Pintado (SERIEs - Journal of the Spanish Economic Association, 2017)
We consider a model of local public goods in a random network context. The influence network determines (exogenously) who observes whom every period and comprises a wide array of options depending on the degree distribution and the in/out-degree correlations. We show that there exists a unique equilibrium level of public good provision and compare it with the efficient level. We derive further insights for this problem by performing a comparative statics analysis.
Keywords: D85; H41; 330; Influence networks; Public goods; Out-degree; In-degree; Best-shot game